2021
DOI: 10.3390/min11060634
|View full text |Cite
|
Sign up to set email alerts
|

Sphalerite Composition in Low- and Intermediate-Sulfidation Epithermal Ore Bodies from the Roșia Montană Au-Ag Ore Deposit, Apuseni Mountains, Romania

Abstract: We evaluated the significance of the iron and manganese content in sphalerite as a tool for distinguishing between low-sulfidation and intermediate-sulfidation epithermal deposits on the basis of new and previously published electron probe microanalyses data on the Roșia Montană epithermal ore deposit and available microchemical data from the Neogene epithermal ore deposits located in the Apuseni Mountains and Baia Mare region, Romania. Two compositional trends of the Fe vs. Mn content in sphalerite were delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In contrast, wurtzite (a high-temperature polymorph of sphalerite) can absorb ~50 mol.% almost without temperature dependence [38]. To the best of our knowledge, this is the highest Mn content (up to 14.1 wt.%) in sphalerite reported within the Golden Quadrilateral ore deposits (up to 6.01 wt.% at Roşia Montană [39]) and the Baia Mare mining district (0.86 wt.% at Şuior [40]). Previously, Cook et al [1] reported up to 6.75 wt.% in Săcărâmb hydrothermal ore deposit.…”
Section: Vibrational Characteristics Of Mn-substituted Sphaleritementioning
confidence: 80%
See 4 more Smart Citations
“…In contrast, wurtzite (a high-temperature polymorph of sphalerite) can absorb ~50 mol.% almost without temperature dependence [38]. To the best of our knowledge, this is the highest Mn content (up to 14.1 wt.%) in sphalerite reported within the Golden Quadrilateral ore deposits (up to 6.01 wt.% at Roşia Montană [39]) and the Baia Mare mining district (0.86 wt.% at Şuior [40]). Previously, Cook et al [1] reported up to 6.75 wt.% in Săcărâmb hydrothermal ore deposit.…”
Section: Vibrational Characteristics Of Mn-substituted Sphaleritementioning
confidence: 80%
“…1. Natural sphalerites of 𝑍𝑛 1−𝑥 𝑀 𝑥 𝑆 (M = Mn, Fe), where x is in the range of 0.0 Mare area [40], and Roşia Montană [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations